Advances in Nanomedicines for Interaction with the Intestinal Barrier. Issue 6 (23rd March 2022) - Lin, Sisi; Wu, Feng; Cao, Zhenping; Liu, Jinyao
Abstract : The intestinal barrier plays a vital role in maintaining the homeostasis of the gut and the organism. Various nanomedicines with advantages in interacting with the intestinal barrier have been developed for disease treatment. Previous studies indicate multiple interactions between these nanomaterials and the intestinal barrier, boosting their applications in promoting the efficiency of oral drug delivery. Recently, numerous elegant nanomedicines have been developed for preventing and treating both intestinal and extraintestinal diseases. Integration of multiple elements with diverse functions into a single type of nanomedicine is beneficial for comprehensive regulation of its interaction with the intestinal barrier and the corresponding treatment efficacy. In this review, the interactions between nanomaterials and the intestinal barrier are discussed following an introduction of the structure and function of the intestinal barrier, with an aim to better understanding the rational design of effective nanomedicines, particularly for oral delivery. Lastly, the applications of oral nanomedicines in treating intestinal barrier dysfunction and relevant diseases, such as inflammatory bowel disease, diabetes, arthritis, and cancer, are highlighted. It is anticipated that this review will stimulate more innovative thinking focused on the intestinal barrier as a critical target for drug delivery and disease treatment. Abstract : To better understand the rational design of nanomedicines, particularly for oral delivery, the interactions between nanomaterials and the intestinal barrier are discussed, followed by an introduction of oral nanomedicines for treating intestinal barrier dysfunction and relevant diseases. This review stimulates more innovative thinking focused on the intestinal barrier as a critical target for drug delivery and disease treatment.